Reduced necrosis and content of apoptotic M1 macrophages in advanced atherosclerotic plaques of mice with macrophage-specific loss of Trpc3 - Solanki, Sumeet (2017)
Fil: Solanki, Sumeet. University of Toledo. College of Medicine and Life Sciences. Department of Physiology and Pharmacology. Center for Hypertension and Personalized Medicine; Estados Unidos